Levels of crystalline silica dust in dental laboratorium of Dental Health Technology Study Program of Vocational Faculty, Universitas Airlangga - Eny Inayati; Sherman Salim; Sonya Harwasih; Sri Redjeki Indiani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Silicosis is an occupational lung disease caused by inhaling particles of crystalline silica in a long time. The disease then results in inflammation and defects in lung tissue. Prosthesis construction is usually conducted in dental laboratory using a lot of materials containing crystalline silica, such as gypsum, ceramics, planting material, sandblast and others. Purpose: This research aims to determine levels of crystalline silica dust in the dental laboratory of Dental Health Technology Diploma Study Program, Vocational Faculty, Universitas Airlangga. Method: Three measurement points was determined, namely point 1, point 2 and point 3 in each dental laboratory space (I and II). Suctioning dust was performed at those points using Low Volume Dust Sampler (LVDS). Samples taken were divided into two groups, namely X and Y. Taking dust samples were carried out for 30 minutes. Elements of crystalline silica contained in the dust were quantitatively measured using XR Defractometry tool, while size and morphology of silica were measured using SEM EDX tool. Data obtained were statistically analyzed by paired t test. Result: The results showed significant differences in the levels of the total dust measured and crystalline silica in the form of quartz and cristobalite among those two dental laboratory spaces. Conclusion: It can be concluded that the levels of the total dust and silica quartz dust in the dental laboratory spaces I and II were greater than the Threshold Limit Value (TLV) determined.